Wykonaj mnożenie i zredukuj wyrazy podobne.
a) c(b+3)+c
b) b(b-4)+3b
c)2a(a-b+5)
d) b b(b-5)-(b+5)
e) -(a-3b)-5(a-2b+5)
f) x do kwadratu (y-2)+3x(xy-4)
g) -1/2a(-2a do kw.+6 a +6)
h) -2/3xy( 6x+3y-9)
i) -1,5abc(2a-4b+6c-8)
j) -2,5xyz(2xy+6yz+4xz)

3

Odpowiedzi

2010-02-11T15:05:38+01:00
A) c(b+3)+c
cb +3c +c = cb + 4c

b) b(b-4)+3b
b² - 4b +3b = b² - b

c)2a(a-b+5)
2a² - 2ab + 10a

d) b b(b-5)-(b+5)
b³ - 5b² - b-5

e) -(a-3b)-5(a-2b+5)
-a +3b-5a+10b -25 = -6a + 13b -28

f) x do kwadratu (y-2)+3x(xy-4)
x²y- 2x² +3x²y - 12x = 4x²y -2x² -12x

g) -1/2a(-2a do kw.+6 a +6)
a³ -3a² - 3a

h) -2/3xy( 6x+3y-9)
-4x²y -2xy² + 6xy

i) -1,5abc(2a-4b+6c-8)
-3a²bc + 6ab²c -9abc² +12 abc

j) -2,5xyz(2xy+6yz+4xz)
5 x²y²z -15xy²z² - 10z²yx²
1 5 1
2010-02-11T15:08:14+01:00
A) bc+3c+c=bc+4c
b)b²-4b +3b=b²-b
c)2a²-2ab+10a
d)b²-5b-5a+10b-25= b²+5b-5a-25
e)-a+3b-5a+10b-25=-6a+13b-25
f) x²y-2x+3x²y-12x=4x²y-14x
g)-a³+3a²+3a
h)-4x²y-2xy²+6xy
i)-3a²bc+6ab²c-9abc²+12abc
j)-5x²y²z-15xy²z²-10x²yz²
  • Użytkownik Zadane
2010-02-11T15:09:45+01:00
A) c+b+3+c= 2cb+3
b) b+b-4+3b=5b-4
c)2a do kwadratu -b+5
d) b do potęgi 4
e)-a+3b-5+a-2b+5= b
f)x do kwadratu -y+3x+xy-6
g)1/2a-2a do kwadratu+12
h)-2/3xy+6x+3y-9
i)-1,5abc+2a-4b+6c-8
j)-2,5xyz+2xy+6yz+4xz